Effectiveness of Educational Intervention Based on Academic Stress and Emotional Intelligence among Senior Secondary School Students of Dibrugarh Town (Assam) - Sinha, Sandip; Yaja, Hage; Hernwal, D. S. (Integrated Journal for Research in Arts and Humanities, 2024)
Average performance of school students and increasing dropout rates are major problems in our country. A poor academic performance and other curricular activities generate negative emotions in young people and results in academic stressors and degrading emotional intelligence. The study aimed to analyze the repercussions of academic stressors on ability to perform among students, to differentiate between academic stress (AS) and emotional intelligence (EI) among students, and finally to establish the impression of EI in this context. A descriptive correlation study involving senior secondary school students of Dibrugarh Town (Assam) affiliated to Secondary Education Board of Assam (SEBA) and CBSE respectively. The sample consisted of 422 students (Boys-209, Girls-213) aging between 14-18 years, who responded through a questionnaire for evaluating the variables of study. The study traced a relationship between both variables among the students. AS and EI of subjects is nearly normally distributed, boys have shown higher AS compared to girls, whereas girls have shown higher EI than boys drawing towards a negative co-relation between AS and EI, respectively.